Contemporary India and South Africa : legacies, identities, dilem mas - Patel, Sujata (New Delhi : Routledge, 2012)
Papers presented at an international conference held in October 2010 .
Includes bibliographical references and index.
Keywords: East Indians -- South Africa -- History -- Congresses; India -- Relations -- South Africa -- Congresses; South Africa -- Relations -- India -- Congresses; South Africa -- History -- Congresses